The influences of Taiwan's National Health Insurance on women's choice of prenatal care facility: Investigation of differences between rural and non-rural areas - Chen Chi-Liang; Chen Likwang; Yang Wei-Chih (BMC, 2008)
Abstract Background Taiwan's National Health Insurance (NHI), implemented in 1995, substantially increased the number of health care facilities that can deliver free prenatal care. Because of the increase in such facilities, it is usually assumed that women would have more choices regarding prenatal care facilities and thus experience reduction in travel cost. Nevertheless, there has been no research exploring these issues in the literature. This study compares how Taiwan's NHI program may have influenced choice of prenatal care facility and perception regarding convenience in transportation for obtaining such care for women in rural and non-rural areas in Taiwan. Methods Based on data collected by a national survey conducted by Taiwan's National Health Research Institutes (NHRI) in 2000, we tried to compare how women chose prenatal care facility before and after Taiwan's National Health Insurance program was implemented. Basing our analysis on how women answered questionnaire items regarding "the type of major health care facility used and convenience of transportation to and from prenatal care facility," we investigated whether there were disparities in how women in rural and non-rural areas chose prenatal care facilities and felt about the transportation, and whether the NHI had different influences for the two groups of women. Results After NHI, women in rural areas were more likely than before to choose large hospitals for prenatal care services. For women in rural areas, the relative probability of choosing large hospitals to choosing non-hospital settings in 1998-1999 was about 6.54 times of that in 1990-1992. In contrast, no such change was found in women in non-rural areas. For a woman in a non-rural area, she was significantly more likely to perceive the transportation to and from prenatal care facilities to be very convenient between 1998 and 1999 than in the period between 1990 and 1992. No such improvement was found for women in rural areas. Conclusion We concluded that women in rural areas were more likely to seek prenatal care in large hospitals, but were not more likely to perceive very convenient transportation to and from prenatal care facilities in the late 1990s than in the early 1990s. In contrast, women in non-rural areas did not have a stronger tendency to seek prenatal care in large hospitals in the late 1990s than in earlier periods. In addition, they did perceive an improvement in transportation for acquiring prenatal care in the late 1990s. More efforts should be made to reduce these disparities.